What do overregularizations tell us about morphological knowledge? - Aguirre, Carmen (Círculo de Lingüística Aplicada a la Comunicación, 2023)
It is suggested that a static vs. dynamic morphology model can offer an adequate explanation of the emergence and evolution of overregularizations in Spanish verbal morphology. On the other hand the development of overregularizations in Spanish supports Dressler’s model of the mental representation of morphology. It is claimed that, in the case of Spanish, overregularizations reveal the beginnings of modularized morphology. It is a form of evidence that a new rule system is emerging in the morphological component, and with it dynamic morphology begins to develop.